STRATEGI PROMOSI OBYEK WISATA MINGGON JATINAN DI KABUPATEN BATANG - Dewi Yuniar Magetana (Fakultas Ekonomi dan Bisnis Universitas Pekalongan, 2023)
Minggon Jatinan tourism object in the first year of its opening gained a fairly large turnover, but in the course of the following years this tourist attraction has decreased a large turnover. This study aims to analyze the promotion strategy of Jatinan Minggon attractions conducted by the manager of Jatinan Minggon. This study is a qualitative approach with descriptive analysis methods. Data collection techniques in this study using observation techniques, interviews, and documentation. Validity techniques using triangulation source triangulation techniques and techniques. Data analysis techniques used are descriptive analytical methods. The results showed that the promotional strategy undertaken by the manager of the Jatinan Minggon the author of the view is interesting but still simple so it has not boosted the amount of turnover as in the early years of the event. More cooperation is needed with the local Department of Culture and Tourism and other agencies in promoting tourism objects Minggon Jatinan